Effects of Warm Versus Cold Ischemic Donor Lung Preservation on the Underlying Mechanisms of Injuries During Ischemia and Reperfusion. Issue 5 (May 2018) - Iskender, Ilker; Cypel, Marcelo; Martinu, Tereza; Chen, Manyin; Sakamoto, Jin; Kim, Hyunhee; Yu, Keke; Lin, Huiqing; Guan, Zehong; Hashimoto, Kohei; Waddell, Thomas K.; Liu, Mingyao; et al.
Abstract : Background: Ischemia-reperfusion injury related to lung transplantation is a major contributor to early postoperative morbidity and mortality. We hypothesized that donation after cardiac death donor lungs experience warm ischemic conditions that activate different injurious mechanisms compared with donor lungs that undergo prolonged cold ischemic conditions. Methods: Rat donor lungs were preserved under different cold ischemic times (CIT) (12 hours or 18 hours), or under warm ischemia time (WIT) (3 hours) after cardiac death, followed by single left lung transplantation. Lung function was analyzed during the 2-hour reperfusion period. Microscopic injury, cell death, energy status, and inflammatory responses were assessed. Results: Pulmonary oxygenation function was significantly worse in both 18hCIT and WIT groups, accompanied by higher peak airway pressure, acute lung injury scores, and expression of cell death markers compared with the 12hCIT control group. In lung tissue, reperfusion induced increased expression levels of interleukin (IL)-1α, IL-1β, IL-6, and chemokines CCL2, CCL3, CXCL1, and CXCL2 in CIT lungs. Notably, these changes were much lower in the WIT group. Additionally, plasma levels of IL-6, IL-18, CCL2, and vascular endothelial growth factor were significantly higher, and adenosine triphosphate levels were significantly reduced in warm versus cold ischemic lungs. Conclusions: Compared with 12hCIT, posttransplant pathophysiology deteriorated similarly in both 18hCIT and WIT groups. However, tissue adenosine triphosphate levels and inflammatory profiling differed between warm versus cold ischemic donor lungs. These differences should be carefully considered when developing specific therapeutic strategies to reduce ischemia-reperfusion injury in lung transplantation. Abstract : The authors compare the different injurious mechanisms induced by warm and cold ischemia in a rat lung transplantation model. It is helpful to develop effective targeted therapies to ameliorate transplant-related IR injury.